MEDIA POT LARANG UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN DAN PENGURANGAN SISWA KELAS 1 SD N 1 SUNYARAGI - Zaelani, Abdul Khavi; Huda, M. Khozinul; Rochmah, Eliya (Cahaya Ilmu Bangsa Institute, 2024)
The background to the problem in this research is the use of learning media that is less interesting in conveying addition and subtraction material so that students become less than optimal and master arithmetic. This research aims to find out how to develop media and the suitability of media as well as interest in the results of developing Pot Prohibited media. This media is used to improve addition and subtraction skills in grade 1 students at SD N 1 Sunyaragi. The results of the research show that the materials for making pot learning media are prohibited from using R&D, the tools needed are styrofoam, Asturo paper, folded paper and Lego. Then the feasibility of the product in the form of a media product by expert validators and material validators on learning product media was obtained by the assessment results by expert validators which were included in the